Qualidade da água em microbacias hidrográficas com diferentes coberturas vegetais - Pastro, Milena Scaramussa (2015)
Water is a resource essential for life on the planet and therefore, studies on the behavior of their quality are of paramount importance. Thus, the aim of this study is to evaluate the water quality in watersheds under different land uses. To this end, four watersheds were selected with different land uses: pasture (surface water source, lentic environment and lotic); Forest regeneration in primary stage (groundwater); forest (ground and surface water in lentic environment); and coffee plantation (groundwater and surface water in lentic and spring environment). The samples were collected every two months, between February 2014 and December 2014 were analyzed: total and fecal coliforms; dissolved oxygen (DO); total nitrogen (Nt); PO4 3- ; turbidity; temperature; pH; Biochemical Oxygen Demand (BOD); Electrical conductivity (EC); total solids (TS); dissolved solids (DS); suspended solids (SS); metals and calcium, magnesium and iron. We conducted a descriptive analysis of each variable in the dry and rainy seasons, with the results compared with the normative standards of the Brazilian legislation, having calculated the Water Quality Index (SEQI) at each collection point. To assist in the interpretation of the large number of variables, we used multivariate statistical analysis by cluster analysis (AA) and principal component analysis (PCA). All collection points had some type of noncompliance with regulations for humano.Os major water quality indices consumption (IQA) were found in the watershed forest area, followed by the watersheds of the coffee area and pasture. In AA, four groups were formed during the rainy season: group 1 formed by springs and groundwater; group 2 formed by lentic the breakfast area and the forest; group 3 formed by lentic environment pasture; and group 4 formed by lotic pasture. In the dry period, three groups were formed: group 1 formed by spring breakfast area, groundwater forest area of the watershed, lentic environments of the watersheds of cafeeicultura and forest; group 2 formed by lentic environment of the pasture area of the watershed; and group 3 formed by the source and lotic the pasture area of the watershed. The difference between the environments was the main factor of influence on the segregation of groups. From the ACP were selected 4 main components explained 73.09% of the total variance of the data. The selected variables were: the EC, turbidity, Mg, Fe, SD, Nt, BOD, pH, fecal coliform, and therefore being related to dissolved salts, pollution by organic matter and pH.